A closer look at the antibiotic‐resistant bacterial community found in urban wastewater treatment systems. Issue 4 (27th February 2018) - Tehrani, Amir H.; Gilbride, Kimberley A.
Abstract: The conventional biological treatment process can provide a favorable environment for the maintenance and dissemination of antibiotic‐resistant bacteria and the antibiotic resistance genes (ARG) they carry. This study investigated the occurrence of antibiotic resistance in three wastewater treatment plants (WWTP) to determine the role they play in the dissemination of ARGs. Bacterial isolates resistant to tetracycline were collected, and tested against eight antibiotics to determine their resistance profiles and the prevalence of multiple antibiotic resistance. It was found that bacteria resistant to tetracycline were more likely to display resistance to multiple antibiotics compared to those isolates that were not tetracycline resistant. Polymerase chain reaction (PCR) was used to identify the tetracycline resistance determinants present within the bacterial communities of the WWTPs and receiving waters, and it was found that ARGs may not be released from the treatment process. Identification of isolates showed that there was a large diversity of species in both the tetracycline‐resistant and tetracycline‐sensitive populations and that the two groups were significantly different in composition. Antibiotic resistance profiles of each population showed that a large diversity of resistance patterns existed within genera suggesting that transmission of ARG may progress by both horizontal gene and vertical proliferation. Abstract : This study investigated the occurrence of antibiotic resistance in three wastewater treatment plants (WWTP) to determine the role they play in the dissemination of ARGs. Identification of isolates showed that there was a large diversity of species in both the tetracycline‐resistant and tetracycline‐sensitive populations and that the two groups were significantly different in composition. Antibiotic resistance profiles of each population showed that a large diversity of resistance patterns existed within genera suggesting that transmission of ARG may progress by both horizontal gene and vertical proliferation.